The Crime of Theft by Workers in the Workplace: A Review of the Concept of Ghulul in Islamic Criminal Law - David Nwanna Dumbiri; Yovani Zela; Jihan Aulia; Yunanta M. Hafiz; Ivan Vaizal (Jurnal Sahabat ISNU SU, 2024)
This study analyzes theft by workers in the workplace not merely as a crime against property (larceny), but as a form of betrayal of trust (fiduciary duty) in the context of Islamic criminal law. Using a normative approach based on literature studies, this journal examines the concept of Ghulul from the perspective of the Qur'an, Hadith and fiqh jinayah literature (Islamic criminal law), then compares it with the construction of theft in the Indonesian Criminal Code. The employment relationship is analyzed through the framework of the ijarah contract, where the worker acts as an amin (trusted party) who has special obligations. This study shows that criminal liability from the perspective of ta'zir (discretionary punishment) provides more comprehensive justice, going beyond mere punishment, including recovery of losses and social sanctions. In addition, the value of trust in the Islamic perspective can strengthen the company's internal control system. In conclusion, Ghulul is a relevant legal instrument to criminalize and prosecute acts of betrayal of trust in modern employment relationships, while also offering an alternative criminal liability that is more in line with substantive justice.